2007
DOI: 10.1093/glycob/cwm049
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-15: an immune system Siglec conserved throughout vertebrate evolution

Abstract: Siglecs are vertebrate cell-surface receptors that recognize sialylated glycans. Here we have identified and characterized a novel Siglec, named Siglec-15. Siglec-15 is a type-I transmembrane protein consisting of: (i) two immunoglobulin (Ig)-like domains, (ii) a transmembrane domain containing a lysine residue, and (iii) a short cytoplasmic tail. Siglec-15 is expressed on macrophages and/or dendritic cells of human spleen and lymph nodes. We show that the extracellular domain of Siglec-15 preferentially recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
179
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 41 publications
1
179
1
Order By: Relevance
“…An important clue came from the presence of a lysine residue in the Siglec-15 transmembrane domain (Lys-273), suggesting an interaction with the transmembrane adapter protein DAP12. Indeed, a recent study demonstrated that upon co-overexpression of epitope-tagged forms of Siglec-15 and DAP12 in 293T cells, a complex could be detected, which was dependent on the presence of Lys-273 (14). We were also able to detect this complex under similar overexpression conditions (data not shown), and we proceeded to determine whether the complex is also present at endogenous expression levels in osteoclasts.…”
Section: Siglec-15 Associates With Dap12 In Osteoclasts and Antibodyimentioning
confidence: 78%
See 1 more Smart Citation
“…An important clue came from the presence of a lysine residue in the Siglec-15 transmembrane domain (Lys-273), suggesting an interaction with the transmembrane adapter protein DAP12. Indeed, a recent study demonstrated that upon co-overexpression of epitope-tagged forms of Siglec-15 and DAP12 in 293T cells, a complex could be detected, which was dependent on the presence of Lys-273 (14). We were also able to detect this complex under similar overexpression conditions (data not shown), and we proceeded to determine whether the complex is also present at endogenous expression levels in osteoclasts.…”
Section: Siglec-15 Associates With Dap12 In Osteoclasts and Antibodyimentioning
confidence: 78%
“…DAP12 serves as a signaling module for a variety of immune receptors by recruiting the kinase Syk and other signaling molecules upon ligand binding to associated receptors (12,13). Siglec-15 contains both a cytoplasmic ITAM as well as a lysine residue in its transmembrane region that permits interaction with DAP12 upon co-overexpression (14). This combination of activating and inhibitory motifs implies that the signaling effects of Siglec-15 are complex.…”
mentioning
confidence: 99%
“…Siglecs are broadly categorized into 2 subsets based on sequence similarity and evolutionary conservation [2]. The first subset includes the sialoadhesin/CD22/myelin associated glycoprotein (MAG) and the recently described Siglec-15 molecule [5], whereas the second subset comprises the CD33-related Siglecs (reviewed in 1). Each of these molecules is also named by an individual Siglec number and some of them have been assigned a CD nomenclature.…”
Section: Introductionmentioning
confidence: 99%
“…Siglec-15 is one of the few Siglec members conserved throughout vertebrate evolution 17) . We reported that Siglec-15 is expressed on myeloid cells (either macrophages or dendritic cells) in lymph nodes, implying its involvement in immune regulation.…”
Section: Siglec-15 In Bone Homeostasis and Cancermentioning
confidence: 99%
“…Their observations strongly suggest that Siglec-15 plays a role in the differentiation of osteoclasts and in the homeostasis of bone mass. Siglec-15 is one of only two Siglecs that are clearly conserved throughout vertebrate evolution 17) . This high degree of conservation of Siglec-15, despite the fact that it is expressed in the immune system exposed to high evolutionary pressures imposed by pathogens, may be explained by its essential function in the maintenance of bones, the very definition of vertebrates.…”
Section: Siglec-15 In Bone Homeostasis and Cancermentioning
confidence: 99%